2016
DOI: 10.5114/fmpcr/63486
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of influenza virus infections in the 2013/2014 and 2014/2015 epidemic seasons in the reporting system, for different age groups in Poland

Abstract: Background. Influenza remains the cause of many seasonal infections, leading even to death, in all age groups, for all patient health states, under all health policies, and in all latitudes. Influenza infection needs to be thought of not only in terms of the loss of health and the exacerbation of existing diseases, but also in terms of the quantifiable financial consequences borne by the state. Objectives. the aim of the study was to compare two influenza seasons: 2013/14 and 2014/15 through an analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Moreover, the analysis of annual trends in influenza incidence and AC was justified by the fact that the dominant influenza virus in Poland in the 2013/2014 and 2014/2015 seasons was the same (AH1N1). 19,20 In 2014, the average AC at the community level in 31 European reporting countries was 91.59% of the total consumption (range, 84.85%-94.67%). Our study showed that in 2014 in Poland, 94.08% of antimicrobials were consumed at the community level.…”
mentioning
confidence: 99%
“…Moreover, the analysis of annual trends in influenza incidence and AC was justified by the fact that the dominant influenza virus in Poland in the 2013/2014 and 2014/2015 seasons was the same (AH1N1). 19,20 In 2014, the average AC at the community level in 31 European reporting countries was 91.59% of the total consumption (range, 84.85%-94.67%). Our study showed that in 2014 in Poland, 94.08% of antimicrobials were consumed at the community level.…”
mentioning
confidence: 99%